Customer engagement of Gen Z Facebook users and its implications to brand awareness for mountain resorts in Negros Occidental - Ongy, Thea
Negros Occidental is a go-to place for tourists. Currently, there are various mountain resorts in the region, but many have little brand awareness. As the number of identical tourist locations and services grows, brand awareness has become more important in the tourism business. Facebook, a social networking platform with more than a billion users, is an ideal medium for marketers, especially those on a light budget, because it doesn't require costly marketing efforts. This aspect led to businesses targeting Generation Z, a technologically dependent group. This study is a destructive, single cross-sectional sample survey research design that will determine the influence of customers' motivational drivers on customer engagement as well as their behavior on Facebook and how it can contribute to customer brand awareness towards mountain resorts. To achieve this, a survey was conducted with 271 Gen Z Facebook users residing in Negros Occidental as respondents. The results show that most Gen Zs usually spend around 1 hour-5 hours on Facebook in a day every 6:00 PM to 9:00 PM. The motivational drivers have high level of influence on customer engagement towards mountain resorts on Facebook. For the segments, the students and those who spend 1-5 hours on Facebook in a day are the most influenced by each of the motivational drivers and also have higher customer engagement towards mountain resort-related content and have higher mountain resort brand awareness on Facebook. There is a positive relationship between motivational drivers and customer engagement towards mountain resorts on Facebook. Overall, it is found that the higher the motivational drivers, the higher the customer engagement and the higher the customer engagement, the higher the brand awareness.